Illegal Levies as a Negative Element Contributing to The Decrease of The Tourism Potential on Madura - Tolib Effendi; Rusmilawati Windari (International Journal of Business, Economics, and Social Development, 2022)
As revealed by the World Economic Forum, there is a correlation between corruption and tourism: the higher the level of corruption of a state, as reflected in the Corruption Perceptions Index of Transparency International, the lower the number of foreign tourists visiting the state. As such, a very strong correlation exists between the community development index, tourism, and the community’s legal awareness on the journey to the eradication of illegal fees. Illegal fees have to date been regarded as something normal in society. Illegal fees have become a regular in every sector, which must be ceased, and this holds true to the tourism sector as well. It is thus become essential to study the correlation between illegal fees in the tourism sector and the undermined tourism potential on Madura.Illegal fees have become part of the systems applied in Indonesia, including in the tourism sector. One of the reasons behind visitors’ disinterest in visiting a tourist attraction is the illegal fees someone imposes there, whether they be in the form of entrance fees or in the form of parking fees. The absence of a price standard allows some irresponsible persons to collect such fees as entrance and parking fees at tourist attractions variably according to the situation that arises in a given time.This paper uses a socio-legal research method to investigate directly into the relationship between illegal fees in the tourism sector and the undermined tourism potential on Madura. Primary data, collected through interviews, survey, and observation, were analyzed descriptively.